HUBUNGAN FUNGSI MANAJERIAL KEPALA RUANGAN DENGAN TINGKAT KEPATUHAN PERAWAT DALAM PENGENDALIAN INFEKSI NOSOKOMIAL - Nelfa Fitria Takahepis; Sri Wahyuni (Universitas Muhammadiyah Manado, 2020)
Nosocomial infection or also called hospital acquired infections (HAIS) is a hospital-acquired infection that occurs in patients who have been hospitalized for at least 72 hours and the patient shows no symptoms of infection at hospital admission Purpose to analyze the Relationship of Managerial Functions of the Head of Room With the Level of Nurse Compliance in the Control of Nosocomial Infection in Rsu Gmim Pancaran Kasih Manado.Descriptive analytic research method that is cross sectional. The sampling technique in this study used accidental sampling. Data collection was carried out by questionnaire and assisted by Observation. Furthermore, the data collected has been processed using SPSS Version 16.0.Chi-square Test results obtained a significant value of p = 0,000 which indicates that p value is smaller than α 0.05.The conclusion in this study there is a relationship between the Managerial Function of the Head of the Room with the Level of Compliance of Nurses in the Control of Nosocomial Infection in the Inpatient Room at the GMIM General Hospital Pancaran Kasih Manado, indicated by the Chi-square Test Results obtained (p) = 0.000 <0.05. The value of 0,000 is below the Alpha value of 5% (0.05).